Change, choice and cash in social care policies: Some lessons from comparing childcare and elder care - Sue Himmelweit; Hilary Land (The Open University, Economics Department, 2010)
In this paper we will discuss how the value placed on increasing `choice' is a major factor determining both childcare and elder care policies, focussing in particular on the increasing emphasis on using cash allowances and tax credits or reliefs to achieve greater diversity of provision and better `value for money'. The use of cash means understanding how families and service providers in the market respond to incentives to provide more care and what choices are important both to those who need care and those who give it. However, as Nancy Folbre has pointed out: 'In order to solve the care problems, we need to understand how markets work, but also how they don't work' (cited in Waerness, 2006 p76 [...]). We therefore begin by examining first, why the cost of care is increasing and second what happens when care is treated in the market as if it were a commodity like any other. Third, what evidence is there about how the capacity of and willingness to care within families is changing. Does it suggest growth or decline? Does state support for care, especially in the form of cash, substitute for or complement family care? Third, we will examine the circumstances in which `cash for care' policies offer meaningful choices both to those giving care and those who need it. By comparing childcare and elder care policies and practices and analysing their differences, it is easier to evaluate the consequences of treating care provision as a means to achieving other policy objectives rather than as a worthy end in itself.
Keywords: 330; Sozialpolitik; Kinderbetreuungseinrichtung; Altenhilfe; Sozialer Wandel; OECD-Staaten